2019
DOI: 10.1155/2019/6037137
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Phytochemical Analysis and Antioxidant Activities of Tamalakyadi Decoction with Its Modified Dosage Forms

Abstract: Background and Objective. Tamalakyadi decoction (TD) is a classical formulation mentioned in authentic traditional medicine text Sarasankshepaya under nasal diseases and used as a remedy for allergic rhinitis. It consists of 12 plant ingredients. Decoction preparations are widely used in Sri Lankan traditional system and considered effective and safe for treating many disorders. However, decoctions have to be used only in fresh state due to shorter shelf life and loss of stability. This decoction preparation m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…TLC is one of the simple and cheap techniques available to detect phytochemical profiles in herbal drugs [6,13] or plants [4,15,16]. Differences in phytochemical constituents were revealed when compared the TLC fingerprint profile of Sharibadi decoction A with that of Sharibadi decoction B (Table 2 and Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…TLC is one of the simple and cheap techniques available to detect phytochemical profiles in herbal drugs [6,13] or plants [4,15,16]. Differences in phytochemical constituents were revealed when compared the TLC fingerprint profile of Sharibadi decoction A with that of Sharibadi decoction B (Table 2 and Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In brief, 20 g from each Sharibadi decoction A and B were taken into separate round bottoms and refluxed with distilled water (100°C) for 4 h and filtered. Each filtrate was subjected to phytochemical screening using standard protocols [5,6] with some modifications.…”
Section: Phytochemical Analysismentioning
confidence: 99%
“…This reconstituted powder also contains the above-mentioned 12 ingredients in almost the same quantities. In order to develop a ready-to-use formulation of the TMD 12, with composition similar to the TMD12 after preparation, three different formulations were developed and analyzed [12]. These included freeze-dried formulation, spray-dried formulation, and Ganasara formulation and detailed physicochemical and phytochemical analysis were performed.…”
Section: Investigational Productsmentioning
confidence: 99%
“…These included freeze-dried formulation, spray-dried formulation, and Ganasara formulation and detailed physicochemical and phytochemical analysis were performed. The results are now published and showed that the freeze-dried formulation is quantitatively and qualitatively closest to TMD 12 [12]. Therefore the freeze-dried formulation was selected for evaluation of clinical efficacy and safety in this clinical trial.…”
Section: Investigational Productsmentioning
confidence: 99%
“…This reconstituted powder also contains the above mentioned 12 ingredients in almost the same quantities. In order to develop a ready to use formulation of the TMD 12, with composition similar to the TMD12 after preparation, three different formulations were developed and analyzed [9]. These included freeze dried formulation, spray dried formulation and Gnanasara formulation and detailed physicochemical and phytochemical analysis were performed.…”
Section: Randomizationmentioning
confidence: 99%